KAPABILITAS DINAMIS SEKTOR PUBLIK : SEBUAH TINJAUAN LITERATUR - Wijaya, Firman Darusman, Chandra (Jurnal Ilmu Administrasi Negara, 2020)
Dynamic Capability in Public Sector: A Literature Review. Dynamic capabilities has been mentioned in the study of strategic management to build competitive advantage in business sector. However, the rapid development of new public management and good governance has made public sector transformed to develop its capacity, where dynamic governance concepts defines capacity as the availability and well-functioning of able people and agile processes that shape dynamic capabilities. The dynamic capabilities development in public sector will support the achievement of better governance through the development of public policies adaptive to the quick-changing organizational environments. This article aims to review and synthesize literatures regarding dynamic capabilities so that they can contribute to the understanding of dynamics capabilities development in the public sector. The study of dynamic capabilities in this article explicitly focuses on the ability of human resources (able people) and the organization’s business processes (agile process) in building adaptive public policies.